Erweiterung eines Hermiteschen Satzes - Naftalewitsch, A. (Lithuanian Mathematical Journal, 1965)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: А. Г. Нафталевич, Обобщение одной теоремы Эрмита A. Naftalevičius, Vienos Ermito teoremos apibendrinimas